APPLICATION OF DECANTER CAKE TECHNOLOGY IN VEGETABLE CULTIVATION IN THE PERINTIS JAYA WOMEN’S FARMERS GROUP (KWT), PANDAN SEJAHTERA VILLAGE, GERAGAI DISTRICT - Made Deviani Duaja; Elis Kartika; Gusniwati; Buhaira; Lizawati (Fakultas Pertanian, 2025)
Every house in KWT Perintis Jaya has a spacious yard, many of which are located near oil palm plantations. The backyards are typically used for raising cows, chickens, and goats, while the front yards are cultivated with various plants, reflecting simple polyculture practices. Land management remains minimal, with vegetable plots rarely maintained or fertilized, resulting in low yields that are only sold at weekly markets. Some women farmers use fertilizers occasionally but inconsistently, resulting in low productivity. To improve yields while supporting low-income women, organic cultivation methods that reduce reliance on chemical fertilizers and production costs are needed. The village has two palm oil mills, PT. Muara Jambi Sawit Sejahtera and PT. Agro Jaya Perdana, which produces abundant plant-based waste. Through education and mentoring, this waste can be converted into organic fertilizer. Decanter Cake (DC) is the most easily transported and decomposed waste, and when enriched with Trichoderma sp., it becomes an effective biofertilizer. Activities at KWT Perintis Jaya include producing and applying DC and Trichoderma sp. in vegetable cultivation. Socially, KWT's active involvement strengthens networks and solidarity, while support from village officials enhances program legitimacy and opens opportunities for additional assistance. Economically, the frequency of daily kale harvests indicates rapid cash flow, making low-cost DC fertilizer adoption beneficial for reducing expenses and increasing profit margins. The target was achieved: 100 kg of Decanter Cake and 10 kg of Trichoderma sp. every two months. Keywords: Pandan Sejahtera village; decanter cake; mycorrhiza; biodecomposer